Structure Design of Parking Building on Delta Areas - Bambang Wuritno (International Conference on Coastal and Delta Areas, 2015)
The case study in this research is Parking building (Tower C), Project Sunter Park View Apartment is a public facility that serves as a parking garage. It located on the Yos Sudarso Street Kav 30A, Sunter Jaya â€“ North Jakarta ( on Delta Areas ). This building consists of 4 floors including the roof plate with a typical floor plan for each level. Floor to floor elevation is 3 meters height, so the total height of the building reach 9 meters height (less than 40 meters height). Review Design Parkingbuilding structure (Tower C) Project Title: "Structure Design OfParking Building Sunter Park View Apartment With The Equivalent Static Analysis Methodâ€ , wherein the influence of earthquakes on structures analyzed by Equivalent Static method based on the Standard Provisions Design for Earthquake Resistance of Building Structures (SNI 03-1726-2002). Structural components of buildings designed by Special Moment Frame System Bearers (SRPMK) based on Procedure for Calculation of Concrete Structure for Buildings(SN03-2847-200). Foundations including the type of float because the soil under the foundation as a whole is a soft clay